The Defect Analysis of Carbonsteel Pipe Welding Connections Using Non-Destructive Testing with the Penetrant Test Method - Nur Ichsan Sumardani; Ngainun Ibnu Setiawan; Bebeh Wahid Nuryadin; Dadan Sumardani (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2020)
In a welding process carried out on metallic materials is sometimes found defects in the material being tested, it is caused by many factors, such as the lack of good materials used and the lack of perfection of the welding process. At testing, it aims to know the surface defects in carbonsteel pipes to know the defects arising after welding. This test is performed with non-destructive tests (NDT) using Dye Penetrant testing method. This test uses 3 types of liquids, including; Cleaner, Penetrant, and developer. The results of these tests will then be observed whether defects occur after welding and what factors affect it. From the test, results there are known 10 locations defects on the surface of the carbonsteel pipe welding with a type of rounded indication of defects that are then followed up by re-welding on indications of such defects.